Cloud accounting adoption in Thai SMEs amid the COVID-19 pandemic: An explanatory case study - Dalinee Sastararuji; Danupol Hoonsopon; Pongsakorn Pitchayadol; Pimsiri Chiwamit (Journal of Innovation and Entrepreneurship, 2022)
The COVID-19 pandemic has altered the way small and medium-sized businesses (SMEs) function. To maintain business efficiency and reduce operating costs in the context of the constraints imposed by the pandemic, SMEs have been forced to embrace new digital technologies. Cloud accounting is becoming an increasingly important business operating tool for SMEs. By adopting cloud-based accounting, SMEs can become more efficient, financially organized, and flexible. This study aims to investigate the factors that have a pervasive influence on cloud accounting adoption among SMEs in Thailand, following the pandemic's effects. This study integrates three technology adoption theories-the Technology-Organization-Environment framework, Diffusion of Innovation theory, and Institutional Theory-and studies them alongside SMEs' unique characteristics. The research employs a qualitative case study method and triangulated sources of evidence. The findings provide important implications for the research community, policymakers, cloud accounting vendors, and SME owners aiming to formulate better approaches to cloud accounting adoption after the pandemic. The results suggest that vendors should focus on SMEs' particular characteristics and needs. By contrast, SMEs should determine the organizational fit of the cloud accounting platform and integrate cloud accounting with other aspects of their operations.
Keywords: 650; Cloud accounting; Diffusion of innovation theory; Institutional theory; SMEs; Technology adoption; Technology-organization-environment framework